Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 12 - Section 12.1 - The Algebra of Functions - Exercise Set - Page 842: 13


$(g\circ h)(0)=0$

Work Step by Step

$g(x)=-2x;$ $h(x)=\sqrt{x}$ $(g\circ h)(0)$ First, find $h(0)$ by substituting $x$ by $0$ in $h(x)$: $h(0)=\sqrt{0}=0$ Find $(g\circ h)(0)$ by substituting $x$ with $0$ in $g(x)$: $(g\circ h)(0)=g(0)=-2(0)=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.